(untitled) (El-Wahat Journal for Research and Studies, 2017)
Popular Culture Is One Of The Pillars Of The Concept Of Loyalty That Breeds And Grows Inside, By Selecting The Nature Of The Relationships That Bind Individuals To Each Other On One Side, And Their Relationship With The State On The Other Hand, In Addition To Determining The Nature Of Individual Responsibility Imposed By These Relationships. And Which Has Become More Distinct In Many People Thoughts And Their Feelings As Well As In Their Practices And Aspirations Of Thinking, Values, Habits, And Beliefs And Even Wisdom With Which They Portrayed The Realities Of Their Past And Their Future, What Contribtes Directly In The Construction And The Progress Of The Society. Keywords - Representations - Belonging- Popular - Culture